Study of interactions between carboxylated core shell magnetic nanoparticles and polymyxin B by capillary electrophoresis with inductively coupled plasma mass spectrometry - Baron, Daniel; Rozsypal, Jan; Michel, Aude; Secret, Emilie; Siaugue, Jean-Michel; Pluháček, Tomáš; Petr, Jan (Journal of chromatography. A, Including electrophoresis and other separation methods, 2020)
In this work, interactions of carboxylated core shell magnetic nanoparticles with polymyxin B sulfate were studied by connecting capillary electrophoresis with inductively coupled plasma mass spectrometry. The interaction was probed by affinity mode of capillary electrophoresis with 25 mM phosphate buffer at physiological pH. 54Fe, 56Fe, 57Fe, 34S, and 12C isotopes were used to monitor the migration of an electroosmotic flow marker and the interaction of the nanoparticles with polymyxin B. The analysis of interaction data showed two distinct interaction regions, one with low polymyxin B concentration, the second with high polymyxin B concentration. These regions differed in the strength of the interaction, 1.49 × 107 M-1 and 1.60 × 104 M-1, and in the stoichiometry of 0.7 and 3.5, respectively. These differences can be explained by the decrease of electrostatic repulsion between nanoparticles caused by polymyxin B. This is also in agreement with the nanoparticles peak shapes: sharp for low polymyxin B concentrations and broad for high polymyxin B concentrations.
Keywords: Mass Spectrometry; hmotnostní spektrometrie; polymyxin B; tlak; Electrophoresis, Capillary; magnetické nanočástice; Polymyxin B; Magnetite Nanoparticles; elektroforéza kapilární; Pressure